The new early-ripening grain sorghum variety “Derzhavnoe” - L. F. Syrkina; L. A. Kosykh; A. K. Antimonov; O. N. Antimonova (Зерновое хозяйство России, 2020)
Grain sorghum is the most important feed and food agricultural crop with a number of advantages. The purpose of the current study was to develop the feed sorghum variety being early-ripening, productive, low height, adaptable, resistant to the main diseases for the arid conditions of the Middle Povolzhie and the Urals. The variety has been developed by the method of individual selection from a hybrid population, which was based on a complex stage hybridization, which included the varieties “Slavyanka”, “Zersta97”, “Perspektivny1”. The current paper has presented the results of the study conducted in 2016–2018 on the plots of the Povolzhsky RIISS. There have been presented the traits and properties of a new grain sorghum variety “Derzhavnoe” sent to the State Variety Testing and intended for cultivation in the Middle Povolzhie and Ural regions. The advantage of the variety is its low height, large productivity, good adaptability, resistance to lodging, to brittle stems and panicles and grain shedding. Grain productivity in the Competitive Variety Testing has averaged 3.55 t/ha, which is higher on 0.73 t/ha than that of the standard variety “Slavyanka” (2.82 t/ha). The grain of the new variety contains 10.6–12.2% of raw protein, 62.8–76.8% of starch and 3.4–3.6% of oil.100 kgof grain contains 128 u. The variety is productive both in wet and dry weather conditions when sown in mid-May by continuous sowing method. The variety is suitable for mechanized harvesting with conventional grain combines both separately and directly.